The History of Social Work Education in Turkey - Kalaycı, Sami (OPUS Uluslararası, 2021)
Since the early years of the 20th century, following the educational studies carried out by Charity Organization in England and New York Philanthropy School in the USA, social work education has been introduced and this kind of education has spread to many other countries in the world. One of those countries including social work education is Turkey. For more than 50 years, thanks to the education act in Turkey, there have been many social workers and conductors. By cooperating with various disciplines and under the leadership of the United Nations, the first school of social work education “Social Services Academy” was launched in 1961 in Turkey. Offering 4-year occupational education following high school, Social Services Academy has been the foundation of social work education, especially Hacettepe University Department of Social Work and contributed to the foundation of other schools in Turkey. This study aims to discuss historical development of social work education in Turkey
Türkiye’de Sosyal Hizmet Eğitiminin Tarihi
Keywords: Social Work Education; Turkey; Social Work History; Social Work